Clinicopathological Study of Thyroglossal Cyst (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Thyroglossal cyst is a congenital malformation that occurs due to incomplete closure of the thyroglossal duct. Apart from quiescent embryological remnant, it presents clinically as a midline cystic swelling that moves with tongue protrusion; present at any age, often requires surgical excision.Objective: To evaluate the clinical features and treatment outcomes of patients with a thyroglossal duct cyst.Material and methods: This observational study was carried out in the Department of Surgery, Dept. of Otolaryngology, Ibn Sina Medical College, Dhaka, A total 40 cases of both sexes with the age 6-67 years, during the period of 2013 to 2018 (5 years)Results: A total 40 cases of thyroglossal cyst with mean age of 24.37 years were included in study. Of the total 40 cases, 20 (50%) patients were male and 20(50%) were female. Most common clinical presentation was painless midline cystic swelling was the main complaint in 30 patients (75%), followed by dysphagia 5 (12.5%), Sore throat 3 (7.5%) and globus 2 (5%) in descending order. Most common location of cyst was in infrahyoid region in 26 patients (65%), suprahyoid in 14 patients (35%).Conclusion: The most common presentation of thyroglossal cyst is a midline cystic swelling that moves with tongue protrusion. The standard surgical approach to thyroglossal cyst is Sistrunk’s operation with low recurrence rate. Malignancy within thyroglossal cyst is very rare but should be rule out in all cases.Bangladesh J Otorhinolaryngol; October 2020; 26(2): 153-157